2012
DOI: 10.2527/jas.2011-4599
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the distance traveled from sale barns to commercial feedlots in the United States and overall performance, risk of respiratory disease, and cumulative mortality in feeder cattle during 1997 to 20091

Abstract: Most beef cattle are transported at least once during their lives, and this potentially stressful practice may affect subsequent health and performance. Limited research is available quantifying the effects of transport on feedlot performance and health, and particularly the risk of bovine respiratory disease complex (BRD), which is the most common disease of weaned calves after arrival to the feedlot. The objective of this retrospective study was to determine potential associations between distance traveled (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 20 publications
6
60
0
4
Order By: Relevance
“…In cohort-level studies, mixed-sex cohorts were at increased risk compared to single-sex cohorts (Sanderson et al, 2008) and all-male cohorts were at increased risk compared to all-heifer cohorts (Cernicchiaro et al, 2012b). In our study, heifer-only and mixed-sex cohorts were restricted to a small number of feedlots and clustered by feedlot; estimates of effect were imprecise so we cannot draw a conclusion about effects of the sex of the cohort on BRD risk.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In cohort-level studies, mixed-sex cohorts were at increased risk compared to single-sex cohorts (Sanderson et al, 2008) and all-male cohorts were at increased risk compared to all-heifer cohorts (Cernicchiaro et al, 2012b). In our study, heifer-only and mixed-sex cohorts were restricted to a small number of feedlots and clustered by feedlot; estimates of effect were imprecise so we cannot draw a conclusion about effects of the sex of the cohort on BRD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, North American studies have identified variation in risk depending on feedlot location (Cernicchiaro et al, 2012b). Feedlot region is likely to be a proxy for many risk factors, including unknown or unmeasured factors, so that much of the effect would be expected to be indirect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations